Layers of Time a history of Ethiopia - Henze, Paul B. (Addis Ababa Shama Books, 2004)
Layers of Time, true to its title, offers a well-balanced overview of the Ethiopian history from the remotest past to modern times... For the subsequent better known phases of Ehiopia's extraordinary and dramatic history, substantial coverage is also provided. The story of the rise and fall of Aksum, an African world power contemporary with Rome and Byzantium, and the subsequent Zagwe and Solomonid Kingdoms of the Ethiopian highlands, are ably sketched out, with proper emphasis on the geographical and cultural elements that influenced local developments. The book concludes with solid and original presentation exploiting the author's own expert knowledge of the events of recent times.
Includes bibliographical references (p. 344-360) and index
Keywords: Ethiopia-History